Equine pythiosis in the eastern wetlands of Uruguay - Romero, Agustín (2019)
Equine pythiosis is an ulcerative and granulomatous disease of the skin, caused by the oomycete Pythium insidiosum (Pythiaceae). The objective of this study was to describe seven cases of equine pythiosis that occurred from 2012 to 2017 in the eastern region of Uruguay. Six of the seven cases occurred in the eastern wetland ecosystems of the Merin basin, and the remaining case occurred in the wetland fluvial plains of the Tacuarembó River. Lesions consisted of a large, rapidly growing ulcerated tumor with abundant granulation tissue, serosanguineous secretion, and fistulous tracts containing large concretions or kunkers. The animals presented intense pruritus, claudication and loss of body condition, with death or euthanasia in extremis in six cases. The main histological lesions consisted of an eosinophilic and pyogranulomatous inflammatory process, with numerous foci of eosinophilic necrosis (kunkers), collagenolysis, and a Splendore–Hoeppli reaction. In all cases, silver coloration (Grocott) showed intralesional hyphae compatible with P. insidiosum, which was confirmed by immunohistochemistry in three cases. A horse in the terminal phase of the disease was treated with triamcinolone acetonide (50mg IM every 15 days), and fully recovered after 1 year. It is concluded that equine pythiosis is prevalent in the wetland ecosystems of eastern Uruguay and that treatment with triamcinolone is auspicious.